2022
DOI: 10.17718/tojde.1137255
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cluster Teaching With Worksheets on Students’ Academic Achievement in Distance Education

Abstract: The aim of this study is to examine the effect of teaching with worksheets prepared for the 6th grade clusters in distance education on the academic achievement of students. The research was conducted with 39 students studying in a public secondary school in eastern Turkiye in the first semester of the 2020-2021 academic year. In the study, a quasi-experimental design with pretest-posttest control group was practiced to collect data. In the experimental group, the subject of cluster was taught with worksheets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…In other words, the primary studies indicated a small but positive effect on teachers' perceptions of distance education and their proficiency in using technology. This finding aligns with previous studies on the topic (Alghamdi et al, 2020;Ali, 2020;Burac et al, 2019;Cachero-Gonzalez et al, 2019;Celik et al, 2022;Elizabeth Noor Coutts et al, 2020;Fis Erumit et al, 2021;Goncalves et al, 2020;Gorghiu et al, 2021;Grabinski et al, 2020;Hamann et al, 2020;Makamure & Tsakeni, 2020;Makokotlela, 2022;Mnguni & Mokiwa, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In other words, the primary studies indicated a small but positive effect on teachers' perceptions of distance education and their proficiency in using technology. This finding aligns with previous studies on the topic (Alghamdi et al, 2020;Ali, 2020;Burac et al, 2019;Cachero-Gonzalez et al, 2019;Celik et al, 2022;Elizabeth Noor Coutts et al, 2020;Fis Erumit et al, 2021;Goncalves et al, 2020;Gorghiu et al, 2021;Grabinski et al, 2020;Hamann et al, 2020;Makamure & Tsakeni, 2020;Makokotlela, 2022;Mnguni & Mokiwa, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Lee et al, 2022) helped increase a user's interaction with emerging technologies. Rapid population growth, epidemics and other factors also required a structural replanning of the world's education systems (Celik et al, 2022). Educators and education stakeholders also believe in the need for replanning rather than the traditional structure in education (Alghamdi et al, 2022;Baleghi et al, 2017;Pittman & Gaines, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As the interview to the lecturers was taken, the lecturers mentioned that an ideal training is needed every semester because to face new challenges in education, especially related to technology development, lecturers must update their professionalism to be more adequate. Lecturers must understand digital education solutions, including online teaching methodologies and how to give online exams which sometimes give problems to students with an Internet connection (Yucel, 2007). In the interview, one of the lecturers has indicated that it is important to remember that not all lecturers immediately feel comfortable using technology and hardware and software in an educational platform.…”
Section: Finding and Resultsmentioning
confidence: 99%
“…In the qualitative data analysis work for SWOT analysis, the "Qualitative Content Analysis" concept was used. The data were analysed within three stages (Yelken et al, 2012)…”
Section: Instrumentation and Data Collectionmentioning
confidence: 99%